Development of Video Media Ecosystem to Improve Science Communication Skills of Elementary School Students: Pengembangan Media Video Ekosistem Untuk Meningkatkan Keterampilan Komunikasi IPA Siswa Sekolah Dasar - Adha Zam Zam Hariro; Zaini Dahlan (Academia Open, 2025)
General Background: In elementary science education, communication skills—such as expressing ideas, discussing, and reasoning based on evidence—are crucial for fostering 21st-century competencies. However, learning in many schools remains dominated by conventional teacher-centered methods, limiting student engagement and understanding of abstract concepts like ecosystems. Specific Background: Previous research on digital media in science learning has focused largely on cognitive gains, with less emphasis on integrating conceptual mastery with communication skill development. Knowledge Gap: Few studies have developed ecosystem learning media for elementary students that are simultaneously valid, practical, and effective in enhancing scientific communication. Aims: This study aimed to design, develop, and evaluate an instructional ecosystem video for fifth-grade students using the 4D model (define, design, develop, disseminate). Results: Validation showed high feasibility (92% media, 88% material), practicality (90.09%), and effectiveness, with learning outcomes increasing from 31.25 to 81.5 (n-gain = 0.73, high category). The media improved both problem-solving and communication skills through interactive, discussion-oriented activities. Novelty: The developed video integrates ecosystem concepts with structured communication training, tailored to the cognitive and engagement needs of elementary learners. Implications: This innovation offers a technology-based alternative resource supporting the Merdeka Curriculum’s vision, with potential for broader implementation through LMS integration and teacher training.Highlight : Educational videos facilitate understanding of ecosystem concepts. This medium has been proven to be valid, practical, and effective for elementary school students. Improves students' communication skills and science learning outcomes. Keywords : Video Media, Ecosystem, 4D Development, Communication Skills, Elementary School